Strengthening The Capacity Of Muhammadiyah Youth Organizations In Mataram City Based On Strategic Mentoring - Hidayat, Rahmad; Dermawan, M Ariy; Hidayat, Sarif; Agustina, Nurillah; Fujiana, Fujiana (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2026)
This community service activity aims to strengthen the capacity of the Mataram City Muhammadiyah Youth Organization in facing contemporary organizational challenges. The main problem identified was the need for increased in-depth understanding of Governance and Compliance, Strategic Planning and Performance Measurement, and Risk Management and Decision Making. The activity methods included mentoring, intensive material provision, and practical training. Evaluation results showed high program effectiveness. The average initial Pre-test score of 50-60 points increased drastically to 75-80 in the Post-Test, reflects significant improvement in understanding towards the very good category. This improvement recommended the adoption of the training module as an organizational standard and a shift in the focus of follow-up to the implementation of field skills.